Aligning Physician and Hospital Incentives: The Approach at Hospital for Special Surgery - Ranawat, Anil S. (Springer-Verlag, 2009)
Healthcare administrators and physicians alike are navigating an increasingly complex and highly regulated healthcare environment. Unlike in the past, institutions now require strong collaboration among physician and administrative leaders. As providers and managers are trained and work differently, new methods are needed to provide the infrastructure and resources necessary to create, nurture, and sustain alignment between them. We describe four initiatives by administrators and physicians at Hospital for Special Surgery to work together in mutually beneficial relationships that help us achieve the highest level of patient care, satisfaction and safety. These initiatives include improving management efficiency through an orthopaedic service line structure, helping individual physicians grow their practices through the demand-office-operating room initiative of the Physicians Service Department, controlling costs through the supply effectiveness policy, and promoting teamwork in innovation through the technology transfer program.